Voracity and Growth Reconsidered - Holger Strulik (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
This article investigates economic performance when enforceable property rights are missing and subsistence needs matter. It shows that if per capita income is sufficiently high, a windfall gain in productivity triggers behavior that leads to higher growth (the normal reaction). The same shock can produce voracious behavior and lower growth when faced by poor economic agents, in particular when their productivity is low and their society is largely fractionalized. This leads to a re-assessment of the voracity effect. Economic and social performance depends no longer on character traits (the assumed curvature of the utility function) as assumed in the earlier literature. Instead, the initial degree of development, the state of technology, and the make up of society are decisive. An extension towards a two-sector economy shows that conditions for an active informal sector of low productivity are much less restrictive than originally thought.
Keywords: O11; O13; D74; P48; 330; economic growth; property rights; common pool resources; voracity; fractionalization